User-focused design principles - Kwon, Minyoung (A+BE | Architecture and the Built Environment, 2020)
Chapter 7 tested the energy demand of possible office typologies. However, the main aim of the thesis is to develop user-focused design principles for energy efficient office renovation. Therefore, it is important to compare the degree of user satisfaction of highly energy-efficient office typologies. Based on the results from chapter 7, chapter 8 introduces design principles that architects, and facility and real estate managers can use to select the combination of parameters with better user satisfaction during a conceptual design stage of office renovation. It contains a database of the different degrees of user satisfaction with thermal, visual, and psychological comfort, according to the combination of design parameters. Section 8.2 explains the design principles considering user satisfaction and energy efficiency. Section 8.3 provides the overview of predicted satisfaction of 144 office combinations. Recommended office combinations based on energy efficiency are explained in section 8.4. Section 8.5 describes the process of application of the design principles: how can designers interpret and use the principles and predicted models for energy-efficient office renovation?